INTERNATIONAL LEGAL COOPERATION AND THE PRINCIPLES OF RECOGNITION AND ENFORCEMENT: LESSONS FROM HEALTHCARE LAW - DOI 10.5935/2448-0517.20200031 - Cooper, Sarah Lucy (Juris Poiesis - Qualis A3, 2020)
This research paper discusses the delivery of adequate healthcare in prisons in the context of compassionate release procedures, which typically allow prisoners to seek early release from prison due to ill-health. It provides an overview of procedures in the United States and England and Wales, and urges that the two jurisdictions co-operate to model best practices for compassionate release.